Fox is framed : a Leo Maxwell mystery - Smith, Lachlan (Smith, Lachlan. Leo Maxwell mystery (Mysterious Press), 2015)
Faced with evidence of stunning prosecutorial misconduct, a San Francisco judge has ordered a new trial for the Maxwell brothers' father, Lawrence, who was convicted of killing their mother twenty-one years before. A prison snitch soon turns up dead, with Lawrence the only suspect, and Leo teams up with hotshot attorney Nina Schuyler to defend Lawrence against murder charges both old and new. Working the streets while Nina handles the action in the courtroom, Leo is forced to confront the darkness at the center of his life as he follows a trail of corruption and danger that leads to the very steps of City Hall. A tense, twist-filled courtroom procedural, Fox Is Framed barrels toward an unexpected conclusion, as Leo struggles to do right both by the law and his blood.